Physical Fitness Levels Do Not Affect Stress Levels in a Sample of Norwegian Adolescents - Østerås, Berit; Sigmundsson, Hermundur; Haga, Monika (Frontiers in Psychology, 2017)
Physical inactivity, low physical fitness and perceived stress during adolescence are presumed to be risk factors for various disorders and subjective health complaints. On the other hand, physical activity and physical fitness, as well as mindfulness qualities, are regarded as prerequisites for health and well-being in children and adolescent, possibly by moderating the negative effects of stress and protecting against stress-related health complaints. Previous studies have suggested gender differences in the relationship between physical activity/physical fitness and psychological variables. The main objective in this study was to evaluate how physical fitness, along with mindfulness qualities (MAAS-A), pain and BMI, relate to stress (PSQ) in adolescents. Secondary objectives were to explore the relationship between physical fitness, mindfulness (MAAS-A) and BMI more explicitly in the study sample, as well as to evaluate possible gender differences. The cross-sectional sample included 102 Norwegian pupils in 10th grade (15 or 16 years). Study measurements were four items from the Test of Physical Fitness (TPF), the Norwegian version of the four-factor Perceived Stress Questionnaire (PSQ), the Norwegian version of the Mindful Attention Awareness Scale-Adolescent (MAAS-A) and BMI (recorded in terms of self-reported height and weight). Additionally, pain was measured in terms of localization, number of pain sites, duration, and intensity (Visual analogue scale; VAS). According to the regression analyses, physical fitness could not explain any variation in stress among the adolescents. Nevertheless, there were some negative associations between one stress factor (lack of joy) and components of physical fitness at a group level, possibly influenced by conditions not measured in this study. As opposed to physical fitness, mindfulness qualities, and to some degree gender, seemed to explain variation in stress among the adolescents. None of the physical fitness components were associated to mindfulness (MAAS-A), but some components seemed negatively related to BMI, particularly among the males. Among the females, higher physical fitness (in terms of endurance) seemed related to reduced number of pain sites. Of note, the cross-sectional design did not allow us to determine any causal direction among the variables.